Integral insulation structure design of metro screen door based on composite materials - SUN Yantong; JIANG Hong; YANG Da; ZHOU Zhengchao; HE Yuehai (机车电传动)
Insulation failure is a common problem currently for screen doors in the metro systems across China, because of the harsh underground working environment. Focusing on obstacles, such as insulation parts prone to failure, difficult troubleshooting and difficult maintenance, this paper proposed a composite material structure design solution with overall insulation targeting insulation failure of the screen door and the subsequent arc striking. The insulation design involving all structural parts was verified feasible and effective by experiments, providing guidance for subsequent insulation protection and safety upgrade of screen doors.